Speech Recognation Pada Pola Warna Dasar Merah Kuning Hijau Dengan Implementasi Sdk 5.1 - Erwin Dwika Putra; Noris Jastrawan (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2018)
Sound can not propagate in space vacuum . These sound waves have valleys and hills , valleys and hills of the fruit will result in one cycle or period . This cycle takes place repeatedly , leading to the concept of frequency . Clearly , the frequency is the number of cycles that occur in one second . The unit of frequency is Hertz , abbreviated Hz . Color can provide powerful information for object recognition . A simple real scheme and identification of matching the image based on the color histogram as proposed by Swain and Ballard . From this study, the authors onclude that the Speech SDK 5.1 is less able to recognize intonation delivered with a level of accuracy that is obtained is average success of 75 % + 65 % + 90 % = 230 % , 230 % / 3 = 76.67 % .Keyword: Sound, Color, Recoginiton